The Profile of a Prospective Teacher Candidate's Digital Literacy: A Case Study on Faculty of Teacher Training and Education of PGRI University of Palembang - Purwanto, Muhammad Bambang; Rosyidin, Iskandar (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2024)
This study aims to evaluate the digital literacy of PGRI Palembang University's potential teacher candidates. Questionnaires are used in this kind of descriptive quantitative study. One hundred randomly selected students from the Faculty of Teacher Training and Education at PGRI University of Palembang served as the research subjects. Digital literacy questionnaires with indicators for managing, generating, integrating, assessing, and accessing information were used to gather data. The correlation product moment used for instrument validation with the outcomes of every questionnaire item is significant (Sig. < 0.05). Positive Pearson correlation and instrument reliability, as measured by Alpha Cronbach's values of 0.750 > 0.50, indicate the validity and reliability of the instrument. A descriptive analysis is performed on the data to find the percentage of each indication. The findings demonstrated that 80% of indicators fell into the essential skills category for information access, 75% of indicators fell into the management category, 74% of indicators fell into evaluation, 73% of indicators fell into integration, 60% of indicators fell into the insufficient skills category, and 70% of indicators fell into communication. These findings demonstrate that PGRI University of Palembang prospective teacher candidates' digital literacy profiles included markers of information creation. Consequently, it is essential to support pupils' digital literacy.